APLIKASI VARIASI PUMAKKAL TERHADAP PERTUMBUHAN FLAME MOSS DI AQUASCAPE DENGAN MEDIA PASIR MALANG SEBAGAI SUMBER BELAJAR - Purdiyanto, Aris; Muhfahroyin, Muhfahroyin; Widowati, Hening; Sutanto, Agus (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
The aquarium is a medium made of glass, which is currently favored by ornamental fish enthusiasts because apart from being easy to make an aquarium, it is also practical. Aquascape is the art of creating underwater scenery in an aquarium area. To ensure the success of creating a beauty from the art of aquascape, it takes many balance factors in the ecosystem of an aquarium. The objectives of this study include knowing whether there is an influence of pumakcal variation on the growth of Flame Moss in aquascape with poor sand media, knowing the most appropriate pumakcal variation for the growth of Flame Moss and analyzing the potential of learning resources for biology learning material for growth and development. From the results of this study, it was found that variations in pumakkal liquid fertilizer had no significant effect on the growth of flame moss plant height, and variations in pumakkal liquid fertilizer had a significant effect on water pH in flame moss plants. The variety of isolates of pumakkal fertilizer with P4 treatment which gave the best effect on the growth of flame moss plant height was the highest average of 6.88 cm. And the variation of pumakkal fertilizer isolate with P5 treatment was found to have the highest pH value of 7.4. And research results can be used as potential sources of learning biology material for growth and developmen. Kata kunci: aquascape, flame moss, organic fertilizer, pumakkal